A Novel Bispecific Immunotoxin Delivered by Human Bone Marrow-Derived Mesenchymal Stem Cells to Target Blood Vessels and Vasculogenic Mimicry of Malignant Gliomas [Retraction] - Zhang Y; Sun X; Huang M; Ke Y; Wang J; Liu X (Dove Medical Press, 2021)
Zhang Y, Sun X, Huang M, Ke Y, Wang J, Liu X. Drug Des Devel Ther. 2015;9:2947–2959. At the request of the authors, the Editor and Publisher of Drug Design, Development and Therapy wish to retract the published article. Concerns were raised regarding duplicated mouse images and cell staining images in Figures 4A and 5A, respectively. The authors were unable to locate the original data for their study and thus were unable to verify the validity of the data. To ensure the integrity of the publication record the authors requested to retract the paper and the editor has agreed with this decision. Our decision-making was informed by our policy on publishing ethics and integrity and the COPE guidelines on retraction. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”. This retraction relates to this paper